Enhancing Digital Literacy in TVET Education Through Feminist Pedagogy - Xu Wenjun; Abdul Rahman, Khairul Anuar; Ariffin, Arihasnida; Hashim, Suhaizal (Online Journal for TVET Practitioners, 2025)
Digital literacy is essential in today’s technology-driven economy, enabling individuals to effectively utilize digital tools for information retrieval, critical thinking, and creative collaboration. Despite its significance, digital literacy in the bakery business sector remains underexplored, with challenges such as aligning university curricula with industry needs and assessing government initiatives in this niche market. This study aims to address these issues by examining the perspectives of bakery business owners on the interaction between universities, industry, and government in promoting digital literacy through the Triple Helix Model. The Triple Helix Model emphasizes the importance of collaboration among academia, industry, and policymakers to foster innovation and skill development. Incorporating feminist pedagogy into this framework further enhances the study’s approach by promoting collaborative learning, inclusivity, and empowerment. Feminist pedagogy’s focus on creating equitable access to digital literacy aligns with the goals of Technical and Vocational Education and Training (TVET) in breaking down traditional gender barriers and encouraging diverse participation in technology-oriented fields. Through a quantitative methodology involving questionnaires administered to 57 bakery business merchants in a prominent bakery district in Malaysia, the study reveals that perceptions of the university’s role in promoting digital literacy are moderate (mean = 3.23), the industry’s role is also moderate (mean = 3.43), while the government’s role is perceived as high (mean = 3.71). The findings highlight the potential of integrating feminist pedagogy within the Triple Helix framework to create a more inclusive and innovative environment where digital literacy serves as a tool for empowerment. This approach not only benefits the bakery business sector but also strengthens TVET’s capacity to cultivate a digitally literate workforce that is adaptable and resilient in an evolving digital landscape.